Coffee Farmers in Gayo Highlands: Comparison of Cultivation Practice between Farmers of Local Gayonese and Javanese Transmigrants - Nazaruddin, Muhammad; Nasution, Abdullah Akhyar; Awaluddin; Kamil, Ade Ikhsan (International Journal of Criminology and Sociology, 2021)
This study aims to describe the comparison of cultural values among coffee farmers with different ethnic backgrounds in Aceh Tengah and Bener Meriah District. The cultural values of coffee farmers who are transmigrants from Java showed different variations compared to those applied by the local Gayonese coffee farmers. Furhermore, this article explains the understanding and practice of cultural values and their implications in the system of coffee cultivation applied by transmigrant farmers from Java and those from local communities. Data was collected by applying ethnographic method through Live In, participatory observation, and indepth interview. The results showed that there were different patterns of cultivation applied by farmers with gayo ethnic and Javanese migrants living in Gayo. The differences lie on the pattern of cultivation and planting, as well as on the symbolization of the coffee tree itself. The most outstanding difference is that local Gayonese coffee farmers apply local wisdom in the practice coffee cultivation and use the four elements of life symbols such as land, water, air and wind when seeing coffee as a source of livelihood in their lives.